VALIDATING PSQ QUESTIONNAIRE FOR ROMANIAN POPULATION - Tibeică Silviu Cătălin; Dana-Gabriela Budala; Carina Balcos; Andreea Tibeică; Ionut Luchian; Monica Tatarciuc; Lupu Iulian Costin; Doriana Agop-Forna; Elena Carausu (Romanian Society of Oral Rehabilitation, 2023)
Introduction. A questionnaire is a standard method for gathering specific information from a survey's target audience. Questionnaires are commonly used by researchers to elicit the information needed to measure the variables or items that make up the study's area of interest and to react to the study's aims. Material and Method. 20 patients were selected from among the patients who attended dental offices in Iasi, between October 2022 and March 2023. Responses were checked for construct validity (including confirmatory factor analysis to check the factor structure of the scale) and internal reliability. Results. Confirmatory factor analysis showed that items loaded on the appropriate factors in a five factor model (doctors, nurses, access, appointments, and facilities). Scores on the specific subscales showed highly significant positive correlations with general satisfaction subscale scores suggesting construct validity. Conclusions. The Romanian versions of the PSQ-46 can be used to measure the patient satisfaction regarding the quality of dental services. PSQ-46 has good psychometric properties and can be used for research in population surveys regarding medical services.